THE INCEPTION OF THE OCEANS AND CO2-ATMOSPHERE IN THE EARLY HISTORY OF THE EARTH - Liu L.-G. (My University, 2004)
After accretion and solidification of a “magma ocean”, the proto-atmosphere of the Earth is modeled to compose of 560 bar of H2O and 100 bar of CO2. The existence of a CO2-rich atmosphere in the early history of the Earth has been envisaged and supported by earlier studies. The results of the present study suggest that the oceans started to grow when the surface temperature of the Earth cooled to below approximately 300–450 °C. This study further suggests that CO2 was removed away from the early atmosphere as a dense supercritical H2O–CO2 mixture during condensation (or the growing ocean), and then formed carbonate rocks in early geological history. The scenario of early growth of the oceans is in line with the geochemical evidence revealed recently from detrital zircons 4.4 Gyr old. A large-scale hydrosphere probably never existed on Venus, and not for long, on Mars. Thus, the atmospheres of these latter planets are composed mainly of carbon dioxide.